Lung Recruitment, Individualized PEEP, and Prone Position Ventilation for COVID-19-Associated Severe ARDS: A Single Center Observational Study - Sang, Ling; Zheng, Xia; Zhao, Zhanqi; Zhong, Min; Jiang, Li; Huang, Yongbo; Liu, Xiaoqing; Li, Yimin; Zhang, Dingyu (Frontiers in Medicine, 2021)
Background: Patients with coronavirus disease 2019 (COVID-19) may develop severe acute respiratory distress syndrome (ARDS). The aim of the study was to explore the lung recruitability, individualized positive end-expiratory pressure (PEEP), and prone position in COVID-19-associated severe ARDS. Methods: Twenty patients who met the inclusion criteria were studied retrospectively (PaO2/FiO2 68.0 ± 10.3 mmHg). The patients were ventilated under volume-controlled mode with tidal volume of 6 mL/kg predicted body weight. The lung recruitability was assessed via the improvement of PaO2, PaCO2, and static respiratory system compliance (Cstat) from low to high PEEP (5–15 cmH2O). Patients were considered recruitable if two out of three parameters improved. Subsequently, PEEP was titrated according to the best Cstat. The patients were turned to prone position for further 18–20 h. Results: For recruitability assessment, average value of PaO2 was slightly improved at PEEP 15 cmH2O (68.0 ± 10.3 vs. 69.7 ± 7.9 mmHg, baseline vs. PEEP 15 cmH2O; p = 0.31). However, both PaCO2 and Cstat worsened (PaCO2: 72.5 ± 7.1 vs. 75.1 ± 9.0 mmHg; p < 0.01. Cstat: 17.5 ± 3.5 vs. 16.6 ± 3.9 ml/cmH2O; p = 0.05). Only four patients (20%) were considered lung recruitable. Individually titrated PEEP was higher than the baseline PEEP (8.0 ± 2.1 cmH2O vs. 5 cmH2O, p < 0.001). After 18–20 h of prone positioning, investigated parameters were significantly improved compared to the baseline (PaO2: 82.4 ± 15.5 mmHg. PaCO2: 67.2 ± 6.4 mmHg. Cstat: 20.6 ± 4.4 ml/cmH2O. All p < 0.001 vs. baseline). Conclusions: Lung recruitability was very low in COVID-19-associated severe ARDS. Individually titrated PEEP and prone positioning might improve lung mechanics and blood gasses.